Analyzing the Impact of Import Tariffs, Trade Dynamics, and Exchange Rates on Economic Growth in Indonesia - Jan Horas Veryady Purba; Mumuh Mulyana; Wahyu Indra Satria (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the multifaceted relationship between import tariffs, trade dynamics, and exchange rates and their collective impact on economic growth in Indonesia. As a developing country integrated into the global economy, Indonesia's growth is heavily influenced by international trade policies and macroeconomic factors. This study investigates how various import tariffs change trade dynamics, which in turn affect Indonesia's economic growth. At the same time, the exchange rate is analyzed as an important mediator that shapes the trade balance and examines the effect of changes in import tariffs on economic growth. The estimation method used is path analysis, using 9 years of historical quantitative data (2016-2024). Econometric modeling and statistical analysis are used to capture the direct and indirect relationships among the variables of interest. This study finds that import tariffs negatively impact Indonesia’s economic growth through various mediating variables, including the trade balance, exchange rate, and US imports and exports. Empirical analysis using Path Analysis reveals that higher tariffs reduce Indonesia’s export volume, restrict foreign market access, and distort exchange rate stability, leading to trade imbalances and depressing GDP growth. In addition, reduced US imports from Indonesia weaken Indonesia’s trade revenues, which affect investment and consumption capacity. The broader economic consequences highlight the need for a strategic trade policy that balances national interests with global competitiveness. These findings provide policymakers with a framework to optimize Indonesia's trade and monetary strategies to ensure sustainable long-term economic growth. Keywords: Import Tariffs, Exchange Rates, Trade Balance, Economic Growth.